Penerapan Metode Qiroati Dalam Meningkatkan Kemampuan Baca Tulis Al Qur’an di Madin Takmiliyah Ar Roudhoh, Kawedusan, Kebumen - Rafika Istiqomah; Siti Fatimah; Benny Kurniawan (IAINU Kebumen, 2023)
The role of the Koran is very important in guiding and directing human life, so learning to read, understand and live the Koran is an obligation. Studying the Koran at a young age is very necessary, given the fast changing times and childhood is an age that is easily shaped and directed. The purpose of this study was to determine the increase in the ability to read and write the Koran with the qiroati method in madin takmiliyah ar roudhoh kawedusan kebumen. This research includes PTK research (Classroom Action Research), the data collection techniques used are observation and interviews on the implementation of learning. The results of the study found that the application of the qiroati method can improve the ability to read and write the Koran in madin takmiliyah ar roudhoh kawedusan kebumen carried out according to the lesson plans that have been made. The results of the analysis showed an increase, i.e. in cycle 1 there were 33% of students who got a complete grade score increased in cycle 2 there were 89% of students got a complete grade score in the ability to read and write the Koran using the qiroati method. So it can be concluded that the qiroati method can improve the ability to read and write the Koran.